PROFIL ORANG TUA SEBAGAI PENDIDIK DALAM PERSPEKTIF ALQUR’AN - Ginda Ginda (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Oldster profile as educator, can also see its role as counsellor or instructor (teacher) for its children. As counsellor and teacher, oldster shall imbed to child soul, about science and needful attitude by a childs in trip its life.